Rape, consumption, and the "Sarajevo war cookbook" : a review of the forum on war, women and rape - V. Dervisovki (Law Text Culture, 1995)
Multicultural bellies, full of tacos, felafel, and chow mein, are sometimes accompanied by monocultural minds. Unthinking Eurocentrism The cluster of issues examined in this paper have to do with the Western responses to and representations of the issue of 'rape camps' in Bosnia, within the wider context of the representation of war in the 'fonner Yugoslavia' , as a site of age-old ethnic hatreds. Within this framework the mainstream feminist response to the 'rape camps' exposes the ethnocentrism and racism that underpins a particular vision of international sisterhood and the depoliticization of the war by the way the category of gender is mobilised in those discussions. On March 8 of this year, Budinski's theatre in Carlton, Melbourne began its series 'Classroom IlIA', which was staged readings of a testimony by Amira. S, a Bosnian nurse held in a 'rape camp'. The readings were to be performed by various feminist luminaries amongst them Blanche D'Alpuget, Joan Kirner, Jocelynne Scutt and Justine Sanders, each of whom, along with others read the same text day after day.